2010
DOI: 10.1021/jm901758f
|View full text |Cite
|
Sign up to set email alerts
|

5-Modified-2′-dU and 2′-dC as Mutagenic Anti HIV-1 Proliferation Agents: Synthesis and Activity

Abstract: With the goal of limiting HIV-1 proliferation by increasing the mutation rate of the viral genome, we synthesized a series of pyrimidine nucleoside analogues modified in position 5 of the aglycone moiety but unmodified on the sugar part. The synthetic strategies allow us to prepare the targeted compounds directly from commercially available nucleosides. All compounds were tested for their ability to reduce HIV-1 proliferation in cell culture. Two of them (5-hydroxymethyl-2'-dU (1c) and 5-hydroxymethyl-2'-dC (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Among a series of eight nucleoside analogues, we previously showed that two of them, hm 5 -dU (compound 3) and hm 5 -dC (compound 6) ( Fig. 1), were able to progressively inhibit HIV-1 replication, most likely by causing lethal mutagenesis (58). Here, we compared six of these compounds, including the two mutagenic nucleosides, using thermal denaturation of short DNA duplexes and extension of a primer annealed to a modified template.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among a series of eight nucleoside analogues, we previously showed that two of them, hm 5 -dU (compound 3) and hm 5 -dC (compound 6) ( Fig. 1), were able to progressively inhibit HIV-1 replication, most likely by causing lethal mutagenesis (58). Here, we compared six of these compounds, including the two mutagenic nucleosides, using thermal denaturation of short DNA duplexes and extension of a primer annealed to a modified template.…”
Section: Resultsmentioning
confidence: 99%
“…As a control, we have also prepared one analogue modified on position 3 (Watson-Crick position) of the base moiety by a carbamoylmethyl group. Interestingly, some of these compounds displayed antiviral activity in cell culture, and two of them displayed antiviral activity in cell culture in a way that was consistent with an accumulation of deleterious mutations in the HIV-1 genome (58).…”
mentioning
confidence: 76%
See 3 more Smart Citations